2020
DOI: 10.1090/proc/14754
|View full text |Cite
|
Sign up to set email alerts
|

Random Gromov’s monsters do not act non-elementarily on hyperbolic spaces

Abstract: We show that Gromov’s monster groups arising from i.i.d. labelings of expander graphs do not admit non-elementary actions on geodesic hyperbolic spaces. The proof relies on comparing properties of random walks on randomly labeled graphs and on groups acting non-elementarily on hyperbolic spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Note that in [45] the previous result is proven under the assumption that X is separable , that is, it contains a countable dense set. However, since the measure μ is countable one can drop the separability assumption, as remarked in [30, Remark 4]. In fact, the only point where separability is used is to prove convergence to the boundary, and one can prove it for general metric spaces from the separable case and the following fact.…”
Section: Background Materialsmentioning
confidence: 99%
“…Note that in [45] the previous result is proven under the assumption that X is separable , that is, it contains a countable dense set. However, since the measure μ is countable one can drop the separability assumption, as remarked in [30, Remark 4]. In fact, the only point where separability is used is to prove convergence to the boundary, and one can prove it for general metric spaces from the separable case and the following fact.…”
Section: Background Materialsmentioning
confidence: 99%
“…In our work, we assume that all spaces are separable in order to apply results from . However, Gruber–Sisto–Tessera [, Remark 4] observe that in the current setting one may drop this hypothesis by replacing X with a separable metric space quasi‐isometric to it.…”
mentioning
confidence: 99%
“…The first major difference was discovered in [15], where it is shown that random Gromov's monsters cannot act non-elementarily on hyperbolic spaces, while infinitely presented graphical small cancellation groups are acylindrically hyperbolic [14].…”
Section: Introductionmentioning
confidence: 99%